Postpamięć i świadkowie zastępczy a współczesne opisy tzw. konfliktu polsko‑ukraińskiego z okresu II wojny światowej - Jarosław Syrnyk (Ksiegarnia Akademicka Publishing, 2021)
Postmemory and Substitute Witnesses in Contemporary Descriptions of the So-Called Polish-Ukrainian Conflict During the World War II